The Influence of Green Accounting and Public Share Ownership on Disclosure of Corporate Social Responsibility (Case Study of Property, Real Estate, and Building Construction Companies IDX 2020-2021) - Naidah, Naida; Razak, linda Arisanti; Nasruddin, Nasruddin (Jurnal Ekonomi Balance, 2023)
This study, conducted by Naidah, Linda Arisanti Razak, and Nasruddin from Muhammadiyah University of Makassar, investigates the impact of Green Accounting and Public Share Ownership on Corporate Social Responsibility (CSR) disclosure among property, real estate, and building construction companies listed on the Indonesian Stock Exchange (IDX) in 2020-2021. Employing a quantitative approach and purposive sampling, 19 companies were selected for analysis. Green Accounting, assessed through environmental cost disclosure, demonstrated a significant positive influence on CSR disclosure, emphasizing the importance of environmental responsibility for building a positive corporate reputation. In contrast, Public Share Ownership, measured by the percentage of shares owned by the public (<5%), did not exhibit a significant effect on CSR disclosure, challenging expectations of increased public ownership leading to more extensive CSR reporting. The study underscores the pivotal role of environmental considerations, as reflected in Green Accounting practices, in shaping CSR disclosure within the examined sector. In the globalized context, companies are encouraged to contribute meaningfully to economic, social, and environmental aspects. The property, real estate, and building construction sector, crucial for economic growth, highlights the significance of aligning corporate practices with environmental responsibility. Recommendations for future research include expanding the study with additional CSR-related variables and exploring other sub-sectors. Incorporating variables like company size and profitability for comparative analyses is suggested. Companies within the sector are advised to prioritize and enhance CSR disclosure for long-term sustainability and positive stakeholder perceptions.